The Listening to music tuned to 440 Hz versus 432 Hz to reduce anxiety and stress in emergency nurses during the COVID-19 pandemic: a double-blind, randomized controlled pilot study: Listening to music to 440 Hz versus 432 Hz in emergency nurses. - Calamassi, Diletta; Li Vigni, Myriam Letizia; Fumagalli, Carlo; Gheri, Flavio; Pomponi, Gian Paolo; Bambi, Stefano (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Healthcare providers in the emergency first response units have been exposed to a considerable stress during the SARS-CoV-2 pandemic. This study was designed to identify the effects of listening to music during the work break compared to the routine break (in the absence of listening to music) on the level of state anxiety and on the vital parameters of the nurses on duty at the operations center.Methods: Randomized, controlled, three-arm, double-blind, single-center clinical study.Healthcare providers were divided into three groups according to study intervention (Group 1: listening to 440Hz music; Group 2: listening to 432Hz music; Group 3: liberal activity).The study was conducted during the working hours of dayshifts in an emergency first response unit station located in Tuscany, Italy. Outcomes were measured against measures of stress (State-Trait Anxiety Inventory – STAIX1), heart rate (HR), respiratory rate (RR), systolic/diastolic blood pressure (SBP/DBP), pain and productivity (Likert Scale) measured at baseline (T0) and at the end of exposure (T1).Results: Overall, 54 healthcare providers were enrolled; 32 females (59.3%); mean age of 39.64 years (SD±9.94); the total measurements performed were 83. The median values of STAI X1 decreased in all the 3 groups from T0 to T1 (Group 1: 34.5 vs. 32, p=0.0001; Group 2: 34 vs. 29, p=0.001; Group 3: 33 vs. 31, p=0.028). In Group 2 a reduction of mean values of respiratory rate and systolic blood pressure was recorded at T1 (-2.714 b/min, p=0.000 and -3.821 mmHg, p=0.031, respectively).Conclusions: Listening to music at 432 Hz is a low cost and short intervention that can be a useful resource to manage anxiety and stress. Further studies are needed to assess medium and long-term effects of listening to music.